Concentration and maximum exposure time of Lutjanus guttatus juveniles to Syzygium aromaticum eugenol - Chacón-Guzmán, Jonathan (2019)
The most efficient doses of eugenol oil from Syzygium aromaticum for surgical sedation in Lutjanus guttatus juveniles were defined, and the minimum exposure time of no return was determined as a source of information to have a safe time range when handling fish during routine work.  A total of 76 juveniles produced in January 2016 with an average weight of 21.61 ± 2.0 g were selected at the Aquaculture and Marine Biotechnology Laboratory of the Marino del Pacífico Park (Gulf of Nicoya). Juveniles were exposed to 25, 100, 175, and 250 mg/L eugenol concentrations in 30 L tanks, and their induction of anesthesia and recovery were monitored. Once the most efficient dose was defined, the maximum exposure time was determined.  Four times of induction were defined for this study: 4, 8, 12, and 16 min, and the recovery threshold was established at 10 min. Eugenol was determined to be an effective anesthetic for rose snapper juveniles with temperatures ranging between 24.0 and 24.8°C. The 25 mg/L concentration was sufficient for partial induction of fish and appropriate to perform less complex routine activities in the handling of snappers, while the most efficient concentration was 100 mg/L, with exposure times no greater than 8 minutes after total anesthesia.